2021
DOI: 10.4049/jimmunol.2100277
|View full text |Cite
|
Sign up to set email alerts
|

IL-15 Trans-Presentation Is an Autonomous, Antigen-Independent Process

Abstract: Positive and Negative Roles of the Trans-Acting T Cell Factor-1 for the Acquisition of Distinct Ly-49 MHC Class I Receptors by NK Cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…SEE contains two distinct binding sites for MHC II and one on the T cell receptor, thereby crosslinking these proteins [ 31 ]. Previously we used this model system to study Kv1.3 enrichment at the IS and IL-15 trans-presentation [ 25 , 32 ]. Here, we found that WT and NON-CON Kv1.3 variants were dominantly localized in the plasma membrane ( Figure 3 A,B), whereas the ΔC mutant exhibited a higher intracellular fraction ( Figure 3 C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…SEE contains two distinct binding sites for MHC II and one on the T cell receptor, thereby crosslinking these proteins [ 31 ]. Previously we used this model system to study Kv1.3 enrichment at the IS and IL-15 trans-presentation [ 25 , 32 ]. Here, we found that WT and NON-CON Kv1.3 variants were dominantly localized in the plasma membrane ( Figure 3 A,B), whereas the ΔC mutant exhibited a higher intracellular fraction ( Figure 3 C).…”
Section: Resultsmentioning
confidence: 99%
“…We used Jurkat CD4 + T cell lines stably expressing different forms of Kv1.3 channels tagged with mGFP at the N-terminus: wild-type (WT), a ΔC mutant (the last 84 amino acids including the PDZ-binding domain deleted), and NON-CON mutant (point mutation in the poreregion (W384F), abolishing conductance but preserving motion of the gating charges). For control experiments, IL-2Rα was stably transfected into Jurkat cells expressing WT mGFP-Kv1.3 by retroviral transduction, as described in [ 32 ]. We used Raji B cells as antigen presenting cells that can form synapses with Jurkat cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…interacting with F-actin are at the periphery of the IS (pSMAC) 59 , although variations occur depending on the T cell type 60,61 . In a similar process, IL-15 transpresentation, an APC expressing the IL-15Rα/IL-15 complex interacts with a T cell expressing the IL-2/15Rβ and γc subunits of the receptor inducing survival signals 22,29 . The molecules participating in these intercellular proteinprotein interactions get enriched at the IS; MHC II and IL-15Rα move jointly to the IS when either ligand (antigen or IL-15) is present 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Using two humanized immunocompetent orthotopic bladder tumor models and a clinically-relevant investigational approach, including use of the fully-human, Fc-optimized anti-CD40 agonist antibody 2141-V11 that is under active clinical evaluation for the treatment of bladder cancer and other indications (NCT05126472, NCT04059588, NCT04547777), we noted substantial improvement in the therapeutic activity of 2141-V11-induced CD40 agonism through concurrent stimulation with exogenous IL-15, including robust generation of both primary and systemic memory responses. This combination therapy approach was found to critically depend on an intact cDC1-CD8 T cell axis, and is likely to be leveraging the observed upregulation (but incomplete occupancy) of surface IL-15Rα, which has been shown to be capable of incorporating exogenous IL-15 into the trans-presentation pathway (42, 43). Other groups have also observed the ability of CD40 agonists to overcome SOCS3-mediated impairment of CD4 T cell help induced by immunotherapy with common cytokine receptor gamma chain (γc) family members like IL-15 (44), providing additional mechanistic support for the combined therapeutic activation of the CD40 and IL-15 pathways.…”
Section: Discussionmentioning
confidence: 99%